Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Universitas Ekasakti Padang - Nur Lilla Yusa; Ahmad Sabandi; Merika Setiawati; Singgih Ginanjar (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Employee performance is a crucial factor in achieving organizational goals. Observations indicate that employee performance at Universitas Ekasakti Padang is suboptimal, suggesting an influence from work motivation and work discipline. This study aims to determine the impact of work motivation and work discipline on employee performance. It employs a quantitative approach and an associative research design. The study population consists of 83 employees, selected using a total sampling technique. Data were collected via a Likert-scale questionnaire and analyzed using descriptive statistics and multiple linear regression. The results show that work motivation has a positive and significant effect on employee performance (Sig. 0.000), whereas work discipline does not have a significant effect (Sig. 0.374); however, work motivation and work discipline combined have a significant simultaneous effect (Sig. 0.001), contributing 16.1% to the outcome. The achievement levels for all three variables fall into the "good" category.